Awareness of Jordanian Surgical Patients about COVID 19 During Peak of Epidemic at JUH - Abdelkarim Aloweidi; Sami Abu Halaweh; Mahmoud Al-Mustafa; Islam Massad; Ibrahim Qudaisat; Ahmad El-Share; Mohammad Rwaidi; Mohammad Yousef; Mazen Al-Nouti; Isam Bsisu; Mohammad Aqel (ACHSM, 2022)
Around the first COVID-19 epidemic in Jordan, we aimed to explore awareness of COVID-19 (knowledge and attitudes) disease, treatment options, and preventive measures among patients who were admitted to Jordan University Hospital (JUH) and planned to undergo elective surgery over a period of 3 months in 2020. This prospective cross-sectional article uses a questionnaire based survey which was provided to and was answered by patients themselves, then collected data was migrated to computer software and analyzed. The sample resulted in 292 patients. More than 95% were aware of the disease and and given age, educational levels and gender, we found no significant differences in knowledge and awareness of COVID-19 and protective and preventive measures. More than 60% of those surveyed were aware of COVID-19 serious complications and risk factors for developing them. Around 28% of patients who were admitted had significant anxiety from having COVID-19. The media appears to largely influence and spread some misconceptions about COVID-19 transmission and claimed therapies.